Hematologic safety of chronic brain‐penetrating erythropoietin dosing in APP/PS1 mice. Issue 1 (1st January 2019) - Sun, Jiahong; Yang, Joshua; Whitman, Kathrine; Zhu, Charlene; Cribbs, David H.; Boado, Ruben J.; Pardridge, William M.; Sumbria, Rachita K.
Abstract: Introduction: Low blood‐brain barrier (BBB) penetration and hematopoietic side effects limit the therapeutic development of erythropoietin (EPO) for Alzheimer's disease (AD). A fusion protein of EPO and a chimeric monoclonal antibody targeting the mouse transferrin receptor (cTfRMAb) has been engineered. The latter drives EPO into the brain via receptor‐mediated transcytosis across the BBB and increases its peripheral clearance to reduce hematopoietic side effects of EPO. Our previous work shows the protective effects of this BBB‐penetrating EPO in AD mice but hematologic effects have not been studied. Herein, we investigate the hematologic safety and therapeutic effects of chronic cTfRMAb‐EPO dosing, in comparison to recombinant human EPO (rhu‐EPO), in AD mice. Methods: Male APPswe PSEN1dE9 (APP/PS1) mice (9.5 months) were treated with saline (n = 11), and equimolar doses of cTfRMAb‐EPO (3 mg/kg, n = 7), or rhu‐EPO (0.6 mg/kg, n = 9) 2 days/week subcutaneously for 6 weeks, compared to saline‐treated wild‐type mice (n = 10). At 6 weeks, exploration and memory were assessed, and mice were sacrificed at 8 weeks. Spleens were weighed, and brains were evaluated for amyloid beta (Aβ) load and synaptophysin. Blood was collected at 4, 6 and 8 weeks for a complete blood count and white blood cells differential. Results: cTfRMAb‐EPO transiently increased reticulocyte counts after 4 weeks, followed by normalization of reticulocytes at 6 and 8 weeks. rhu‐EPO transiently increased red blood cell count, hemoglobin and hematocrit, and significantly decreased mean corpuscular volume and reticulocytes at 4 weeks, which remained low at 6 weeks. At 8 weeks, a significant decline in red blood cell indices was observed with rhu‐EPO treatment. Exploration and cognitive deficits were significantly worse in APP/PS1‐rhu‐EPO mice. Both cTfRMAb‐EPO and rhu‐EPO decreased 6E10‐positive brain Aβ load; however, cTfRMAb‐EPO and not rhu‐EPO selectively reduced brain Aβ1‐42 and elevated synaptophysin expression. Discussion: Chronic treatment with cTfRMAb‐EPO results in better hematologic safety, behavioral, and therapeutic indices compared with rhu‐EPO, supporting the development of this BBB‐penetrable EPO analog for AD. Highlights: Chimeric monoclonal antibody against the mouse TfR (cTfRMAb)‐erythropoietin (EPO) is a brain‐penetrating IgG‐EPO fusion protein. Chronic treatment with cTfRMAb‐EPO does not alter hematology indices in APP/PS1 mice. Equimolar dose of recombinant human EPO significantly alters hematologic indices in APP/PS1 mice. Both cTfRMAb‐EPO and recombinant human EPO reduce amyloid beta load in APP/PS1 mice. cTfRMAb‐EPO selectively reduces amyloid beta (1–42) and increases synaptophysin in APP/PS1 mice.